The Utilization of U-Dictionary Application in Pronunciation Practices: Student’s Perspective - Caroline Cem; Beguin Sophie; Vandenhove Sophie (Yayasan Adra Karima Hubbi, 2023)
This study explores students' perspectives regarding using U-Dictionary in learning pronunciation. The research employed a quantitative approach, utilizing a survey research method. The sample consisted of 32 sixth-semester students majoring in English Education at University in Asia. The selection of participants was conducted through random sampling to ensure a representative sample. A questionnaire was developed as the research instrument to collect the necessary data. The questionnaire was designed to gauge students' perspectives regarding using U-Dictionary in pronunciation practice. It employed a Likert scale format and was administered to students in the English Teaching Department. This research revealed that students hold a highly positive perception of using U-Dictionary in pronunciation practice. The results indicate that U-Dictionary is perceived as an effective tool for enhancing pronunciation skills among students. These findings provide valuable insights into the students' perspectives and highlight the potential benefits of incorporating U-Dictionary into language learning environments.